A Complete Concordance to Shakespeare - Bartlett, John. author. aut Link
XVI, 1909 p.
Keywords: A complete concordance or verbal index to words, phrases and passages in the dramatic works of Shakespeare. There is also a supplementary concordance to the poems. This is an essential reference work for all students and readers of Shakespeare.